Historical framework of education for people with visual disabilities in Costa Rica - González Vides, Leonela Isarina (2022)
This bibliographic review article explores information from documents, research projects, and scientific contributions with the purpose of determining the history of education for people with visual disabilities in the Costa Rican context. The document introduces a conceptual approach of the facts that represented milestones in the history of education for people with visual disabilities in Costa Rica, in agreement with the paradigms of disability: the early stages of special education from the traditional paradigm, the change toward the rehabilitation paradigm, and the transformation of education from a social model based on human rights. The methodology consisted of a reflexive and analytical study of the publications found throughout the work stages, which facilitated the development of the theme; furthermore the compilation and selection of representative information to establish a conceptual-historical framework. For this, the relevant conceptual units were determined and analyzed. In conclusion, it is important to establish the creation of a reference framework to better understand the social and educational circumstances that Costa Rican society has gone through, share the findings and have greater elements to discern the path to follow, and to help build a fair and inclusive society.